Urine Metabolomics Analysis in Patients With Normoalbuminuric Diabetic Kidney Disease - Feng, Qian; Li, Yuanmeng; Yang, Yuwei; Feng, Jiafu (Frontiers in Physiology, 2020)
Objective: Diabetic kidney disease (DKD) leads to low high albuminuria and gradually progresses to very high albuminuria with kidney insufficiency. However, about 20% -40% of DKD is normoalbuminuric DKD (NADKD), which has impaired kidney function, but normal urine albumin. This study is to investigate the urine metabolomic profiles of patients with NADKD and albuminuria DKD (ADKD). Methods: Totally, 95 patients were divided into simple diabetes mellitus group (SDM group), ADKD group and NADKD group. All subjects were analyzed for urine metabolites using non-targeted metabolomics based on Ultra performance liquid chromatography-tandem mass spectrometry. Results: The urine metabolomic profiles of the SDM group, NADKD group and ADKD group were significantly different, and 65 different metabolites were identified among the three groups. Metabolic pathway analysis of these differential metabolites found that the top three significantly changed metabolic pathways were linoleic acid metabolism, citrate cycle, and, arginine and proline metabolism. There are 12 metabolites enriched in these three metabolic pathways. In detail, compared with the SDM group, the levels of γ-linolenic acid in the ADKD group were increased significantly, while the levels of succinic acid, cis-aconitic acid, citric acid, L-proline, L-erythro-4-hydroxyglutamate, N-methylhydantoin, N-carbamoylputrescine, spermidine and 5-aminopentanoic acid were reduced significantly; compared with the NADKD group, the levels of linoleic acid, γ-linolenic acid and L-malic acid in the ADKD group were increased significantly (P<0.05), while the levels of L-proline, L-erythro-4-hydroxyglutamate, N-carbamoylputrescine and spermidine were significantly reduced (P<0.05). However, there were no significant difference between SDM group and NADKD group (P>0.05). Conclusion: The urine metabolomic profiles between the NADKD group and the ADKD group are significantly different. Especially, these two groups have distinct levels of linoleic acid, γ-linolenic acid, L-malic acid, L-proline, L-erythro-4-hydroxyglutamate, N-carbamylputrescine and spermidine.